ANALISIS YANG MEMENGARUHI IMPOR JAGUNG DI INDONESIA TAHUN 2000-2019 - Maulana Risal Naufal; Mardiana Mardiana; Darmayuda Darmayuda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to analyze and determine the effect of the Indonesia's Gross Domestic Product and real exchange rate on corn imports in Indonesia in 2000-2019. The variables observed in this study are the volume of corn imports as the dependent variable, then the Indonesia's Gross Domestic Product and real exchange rate as an independent variable. This study uses secondary data in the form of time series in annual form from 2000-2019 obtained through the publication of the Central Statistics Agency, Bank Indonesia, and World Bank. The model uses time series data which is calculated by the multiple regression method using Eviews application version 10. The results of this study indicate that simultaneously the Indonesia's Gross Domestic Product and real exchange rate significantly influence corn imports in Indonesia in 2000-2019. Partially, the Indonesia's Gross Domestic Product have a significant positive effect on corn imports in Indonesia in 2000-2019, while real exchange rate variable has a negative and significant effect on corn imports.Keywords: Imports, Gross Domestic Product, Real Rupiah Exchange Rate against US Dollar